Content analysis of Journal of Genetic Counseling research articles: A multi‐year perspective. Issue 3 (15th December 2020) - Wallgren, Alexandra; Veach, Patricia McCarthy; MacFarlane, Ian M.; LeRoy, Bonnie S.
Abstract: Content analyses of published papers in journals inform readers, editors, and members of the profession about historical publication patterns and how the journal has represented the field. This study is a content analysis of original research papers published in the Journal of Genetic Counseling from January 2011 through December 2017. This is the first study of its kind for the flagship journal of the National Society of Genetic Counseling. Of 794 papers published in the 7‐year period, 428 were original research included in the analysis. Content analysis yielded categories reflecting the types of data analyses, genetic counseling practice specialties, characteristics of the study sample, and major topics/issues investigated in each study. There was an overall positive linear trend in the number of articles published during this period ( p  = .002). Approximately equal percentages of studies used qualitative (34%), quantitative (31%), and mixed (35%) analyses, and these proportions did not vary significantly across volumes ( p  = .73). Cancer (27%), prenatal (13.3%), and general genetics (12.6%) were the most prevalent specialties represented. The number of studies about prenatal and pediatrics was less, and the number of studies about neurogenetics was greater than would be expected based on the clinical workforce ( p <.001). Patients were the most common sample (55.6%). While there was a significant increase in the number of articles with diverse samples ( p  = .001), the proportion of such articles did not increase over time ( p  = .86). The most common content areas were genetic counseling practice (16.8%); attitudes, perceptions, and beliefs about genetics services (16.1%); and decision‐making (14.5%). In contrast, relatively few studies focused on laboratory genetic counselor, male, gender non‐conforming, and adoptee populations. The trends and gaps highlighted in this content analysis can inform future research endeavors.